Erratum to: The blocking effect in associative learning involves learned biases in rapid attentional capture. Issue 2 (February 2019) - Unknown
Luque, D., Vadillo, M, A., Gutiérrez-Cobo, M, J., Le Pelley, M, E. (2018). The blocking effect in associative learning involves learned biases in rapid attentional capture. Quarterly Journal of Experimental Psychology, 71, 522—544. doi: 10.1080/17470218.2016.1262435. The above article is part of the Special Issue on Associative Learning (in honour of Nick Mackintosh) and was inadvertently published in the February 2018 issue of Quarterly Journal of Experimental Psychology. After publication of the Special Issue, an online collection on Associative Learning will be created on SAGE Journals and this paper will be included in that collection. The Publisher apologises for this error.